Multicultural Literacy Learning Model Based on Indonesian Folktales in Elementary School Indonesian Language Learning - Nashrullah; Noor Alfulaila; Puji Sri Rahayu (Language, Technology, and Social Media, 2026)
This study aims to develop and test the effectiveness of a multicultural literacy learning model based on Indonesian folklore in Indonesian language learning in elementary schools. The study employed a Research and Development (R&D) approach with the ADDIE model, encompassing analysis, design, development, implementation, and evaluation. The subjects consisted of 60 fifth-grade students from two elementary schools in Palu, two practicing teachers, and three expert validators. Data were collected through validation sheets, practicality questionnaires, literacy tests (pretest–posttest), a multicultural attitude scale, observation, and documentation. Data were analyzed descriptively, using paired t-tests, and calculating effect sizes (Cohen's d). The results showed that the developed model had a very high level of validity (93%) and excellent practicality (89%). The effectiveness test demonstrated a significant increase in students' literacy skills (p < 0.001) with a large effect size, particularly in the interpretation of cultural values and the production of reflective texts. Furthermore, there was a significant increase in students' multicultural attitudes, particularly in the aspects of tolerance and cross-cultural empathy. These findings indicate that integrating Indonesian folklore within a critical literacy framework can strengthen literacy competencies and build multicultural awareness in elementary school students. This model contributes theoretically to the development of culture-based literacy and practically provides an innovative alternative for contextual and transformative Indonesian language learning.